Kincir Perkalian: Inovasi Media Pembelajaran untuk Meningkatkan Minat Belajar Matematika Siswa Sekolah Dasar - Utami, Tri; Zahra, Febrian Haninda Nabila; Nugraheni, Indah Agustin; Damayanti, Zahra (Universitas Sebelas Maret, 2025)
Elementary school students often show low interest in learning mathematics, especially in understanding multiplication operations. One way to address this issue is by using interactive learning media that is relevant to everyday life. Literature reviews indicate that the *Multiplication Wheel* has great potential to increase students' participation and understanding by presenting multiplication concepts in a fun, engaging, and contextual way. The purpose of this study is to evaluate the potential and effectiveness of the Multiplication Wheel in improving students’ interest and learning outcomes in mathematics. This study uses a descriptive qualitative approach with fifth-grade elementary students as participants, and the data were collected through observation and questionnaires, then analyzed descriptively. Based on the reviewed sources, this media can support visual and manipulative learning, provide enjoyable learning experiences, and encourage students’ active involvement. Therefore, the Multiplication Wheel can serve as an effective alternative learning media suitable for the characteristics of elementary school students.Ketertarikan siswa SD terhadap pelajaran matematika seringkali rendah, terutama dalam memahami operasi perkalian. Salah satu cara yang dapat digunakan adalah media pembelajaran yang interaktif dan relevan dengan kehidupan sehari-hari. Tinjauan pustaka menunjukkan bahwa Kincir Perkalian memiliki potensi besar dalam meningkatkan partisipasi dan pemahaman siswa, serta menyajikan perkalian dengan cara yang menyenangkan dan kontekstual. Tujuan dari penelitian ini adalah untuk mengevaluasi potensi dan efektivitas Kincir Perkalian terhadap minat dan hasil belajar siswa SD melalui pendekatan kualitatif deskriptif dengan peserta siswa kelas V, menggunakan instrumen observasi dan angket, serta dianalisis secara deskriptif. Berdasarkan hasil studi pustaka, media ini mendukung pembelajaran visual dan manipulatif, serta mendorong keterlibatan aktif siswa. Oleh karena itu, Kincir Perkalian dapat menjadi media alternatif yang efektif dan sesuai dengan karakteristik siswa usia sekolah dasar.